Review of Chemistry Learning Modules on the Impact of Students' Literacy - Wulandari Nabila, Putri; ., Wiji; Widhiyanti, Tuszie; Mulyani, Sri (KnE Social Sciences, 2024)
This study aimed to review the chemistry learning module that impacts students’ literacy. The method used was document analysis and included articles between 2012 –2022. 20 articles, consisting of 17 journals and three proceedings, were analyzed. Eight articles were indexed by Scopus, and SINTA accredited 12. The main variables analyzed included module development methods, types of literacy skills, and the relationship between development methods and literacy skills. The results indicated nine methods: multi-representation-based modules, natural sciences, STEM, green chemistry, context-based learning, socio-scientific issues, cooperative learning, inquiry, and literacy-based. The types of literacy skills were grouped based on the competencies published by PISA, which included explaining phenomena (about 19 articles), designing investigations (about 18 articles), and evaluating contextual investigations (about 19 articles). The relationship between the development method and the type of literacy skills training shows a connection at each step. The modules developed have the impact of training and improving student literacy. Keywords: chemistry, module, literacy